Short-term physiological responses of Pinus koraiensis Siebold & Zucc. and Chamaecyparis obtusa (Siebold & Zucc.) Endl. seedlings to elevated CO2 - Iereh Kim; Myeongja Kwak; Juyeong Kim; Suyoung Woo (Frontiers in Forests and Global Change, 2025)
Because Pinus koraiensis and Chamaecyparis obtusa are key species for economic forest plantations in Korea, understanding their responses to elevated CO2 is critical for future forest planning. Using seedlings grown in a controlled phytotron environment, we examined gas exchange, chlorophyll fluorescence, photopigment contents and biomass under elevated CO2 conditions. Initially, both species showed no significant differences in net photosynthesis (Anet). P. koraiensis prioritized leaf structural development and showed CO2 induced stress, reflected in altered chlorophyll fluorescence, before showing enhanced photosynthesis following leaf maturation. C. obtusa initiated early biochemical adjustments, indicated by increased biochemical parameters of photosynthesis (maximum carboxylation rate, Vcmax; electron transport capacity, Jmax; and triose phosphate utilization, TPU), yet required more time for these changes to result in higher photosynthetic rates. By the mid-stage, both species under elevated CO2 surpassed ambient conditions in Anet, their ability to capitalize on elevated CO2. As seasonal dormancy begins, C. obtusa exhibited reduced physiological activity and a decline in photosynthetic rates. Notably, enhanced biochemical traits did not translate into increased biomass in either species, likely due to nutrient constraints or elevated respiratory costs. Meanwhile, P. koraiensis exhibited an overall increase in photosynthesis at later stages, mainly driven by developmental timing rather than CO2 itself. These findings underscore species-specific acclimation patterns and suggest that P. koraiensis may be more suited to benefit from future CO2 enrichment than C. obtusa, informing targeted strategies in climate-resilient forest management.